KETAHANAN HIDUP MASYARAKAT KAMPUNG ADAT CIRENDEU DALAM PERSPETIF ANTROPOLOGIS - Gibran Ajib Jabbaril (Jurnal Budaya Etnika, 2018)
ABSTRACT A portrait of the life of the Cireundeu Indigenous Village community located in Cimahi City, 15 km from the city of Bandung, is a corner of a cultural phenomenon that is unique to its variety of customs and traditions. The habit of the people in this village is unique, because the staple food is not rice as other communities around it. They also have strong environmental management procedures, spatial concepts, and customary rules, especially in regional development, patterns of diversification of food, staple food, and other activities that are strictly adhered to from generation to generation. The staple food of this community is rasi (cassava rice). This research was carried out by observing the patterns of consumption and food production in the Cireundeu Indigenous Village Community in the efforts of local food security, as well as analyzing the strengthening and weakening factors related to food self-sufficiency in the village. The method used is the primary survey with observation, interviews with traditional leaders, distributing questionnaires to 36 local respondents. Other analytical methods are spatial analysis and calculation of food deficit surplus. The Research results show that Cireundeu Indigenous Village Wisdom contributes to good food self-sufficiency and diversification with sufficient numbers and even a food production surplus, the follow-up of food self-sufficiency is the growth of the local economy based on local raw materials, food independence, and the growth of home industries and tourism activities. Keywords: Cireundeu Local Culture, Ancestral Traditions, Food Self-Sufficiency.  ABSTRAK             Potret kehidupan  masyarakat Kampung Adat Cireundeu yang berlokasi di Kota Cimahi, berjarak 15 km dari Kota Bandung, adalah sebuah sudut fenomena budaya yang memiliki keunikan dengan ragam adat dan tradisinya. Kebiasaan masyarakat di kampung ini terbilang unik, karena makanan pokoknya bukan nasi sebagaimana masyarakat lain di sekitarnya. Mereka juga memiliki tata cara pengelolaan lingkungan, konsep tata ruang, dan aturan adat yang cukup kuat, khususnya dalam pembangunan kawasan, pola diversifikasi pangan, makanan pokok, dan kegiatan lainnya yang ditaatinya secara ketat secara turun temurun. Makanan pokok masyarakat ini adalah rasi (beras singkong). Penelitian ini dilakukan dengan pengamatan terhadap pola konsumsi dan produksi pangan pada Masyarakat Kampung Adat Cireundeu dalam upaya ketahanan pangan lokal, serta melakukan analisis  terhadap faktor-faktor yang menguatkan dan melemahkan terkait swasembada pangan di kampung tersebut. Metode yang dilakukan yaitu survei primer dengan observasi, wawancara dengan tokoh adat, penyebaran kuesioner kepada 36 responden lokal. Metode analisis lainnya adalah analisis tata ruang dan perhitungan surplus defisit pangan. Hasil Penelitian menunjukan bahwa Kearifan Budaya Lokal Kampung Adat Cireundeu memiliki kontribusi terhadap swasembada dan diversifikasi pangan yang baik dengan angka kecukupan bahkan surplus produksi pangan, kegiatan ikutan dari swasembada pangan ini adalah tumbuhnya ekonomi lokal berbasis bahan baku setempat, kemandirian pangan, dan tumbuhnya industri rumahan serta kegiatan pariwisata.Kata Kunci: Budaya Lokal Cireundeu,Tradisi Leluhur,  Swasembada Pangan.